9
$\begingroup$

I have deduced numerically (See also Wolfram) that we have $$\lim_{r\to0}\frac1r\left(1-\frac1{\binom{n}{r}}\right)=H_n$$ where $H_n$ denotes the $n$th Harmonic number and we define the binomial coefficient by $$\binom{n}{r}=\frac{\Gamma(n+1)}{\Gamma(r+1)\cdot\Gamma(n-r+1)}$$ Has anyone seen this result or similar elsewhere in mathematical literature? Is it possible to analytically prove this result? Would this result be any useful for calculating $H_n$ explicitly (especially for complex arguments)?

$\endgroup$
3
$\begingroup$

We can write $$ \eqalign{ & {1 \over r}\left( {1 - {1 \over {\left( \matrix{ n \cr r \cr} \right)}}} \right) = {1 \over r}\left( {1 - {{\Gamma \left( {r + 1} \right)\Gamma \left( {n - r + 1} \right)} \over {\Gamma \left( {n + 1} \right)}}} \right) = \cr & = \left( {{{\Gamma \left( {n + 1} \right) - \Gamma \left( {r + 1} \right)\Gamma \left( {n + 1 - r} \right)} \over {r\,\Gamma \left( {n + 1} \right)}}} \right) = \cr & = {1 \over {\Gamma \left( {n + 1} \right)}}\left( {{{\Gamma \left( {n + 1} \right) - \left( {1 - \gamma \,r + O(r^{\,2} )} \right)\Gamma \left( {n + 1 - r} \right)} \over r}} \right) = \cr & = {1 \over {\Gamma \left( {n + 1} \right)}}\left( {{{\Gamma \left( {n + 1} \right) - \Gamma \left( {n + 1 - r} \right)} \over r} + \gamma \,\Gamma \left( {n + 1 - r} \right) + O(r)\,\Gamma \left( {n + 1 - r} \right)} \right) \cr} $$

and thus $$ \eqalign{ & \mathop {\lim }\limits_{r\, \to \,0} \;{1 \over r}\left( {1 - {1 \over {\left( \matrix{ n \cr r \cr} \right)}}} \right) = \mathop {\lim }\limits_{r\, \to \,0} {{\left( {{{\Gamma \left( {n + 1} \right) - \Gamma \left( {n + 1 - r} \right)} \over r}} \right)} \over {\Gamma \left( {n + 1} \right)}} + \gamma = \cr & = \psi (n + 1) + \gamma = H_{\,n} \; \cr} $$

$\endgroup$
4
$\begingroup$

Let's use Beta function:

$$\frac1{\binom{n}{r}}=\frac{(n-r)! r!}{n!}=\frac{\Gamma(n-r+1) \Gamma (r+1)}{\Gamma (n+1)}=r B(r,n-r+1)=$$

$$=r \int_0^1 t^{r-1} (1-t)^{n-r} dt$$

We also can write:

$$1=r \int_0^1 t^{r-1} dt$$

Which gives us:

$$\lim_{r\to0}\frac1r\left(1-\frac1{\binom{n}{r}}\right)=\lim_{r\to0} \int_0^1 t^{r-1} \left(1-(1-t)^{n-r} \right) dt=$$

$$=\int_0^1 \frac{1-(1-t)^n}{t} dt=\int_0^1 \frac{1-t^n}{1-t} dt=H_n$$

As per the usual definition of Harmonic numbers.

$\endgroup$
  • $\begingroup$ Very nice and simple approach (+1) $\endgroup$ – Ali Shather Aug 4 at 9:36
  • $\begingroup$ @AliShather, thank you. That trick with $1=r \int_0^1 t^{r-1} dt$ can be very useful $\endgroup$ – Yuriy S Aug 4 at 11:54
  • $\begingroup$ @YuriyS: yes, indeed that's a clever trick $\endgroup$ – G Cab Aug 6 at 11:20
4
$\begingroup$

You could even get more than the limit itself since, for $r$ close to $0$ $$\binom{n}{r}=1+r H_n+\frac{1}{12} r^2 \left(6 \left(H_n\right){}^2-6 \psi ^{(1)}(n+1)-\pi ^2\right)+O\left(r^3\right)$$

$$\frac 1{\binom{n}{r}}=1-r H_n+\frac{1}{12} r^2 \left(6 \left(H_n\right){}^2+6 \psi ^{(1)}(n+1)+\pi ^2\right)+O\left(r^3\right)$$ $$\frac1r\left(1-\frac1{\binom{n}{r}}\right)=H_n-\frac{1}{12} r \left(6 \left(H_n\right){}^2+6 \psi ^{(1)}(n+1)+\pi ^2\right)+O\left(r^2\right)$$

$\endgroup$
3
$\begingroup$

We can apply L'Hôpital's rule in the $0/0$ indeterminate form case giving $$\lim_{r\to0}\frac{1-1/\binom{n}{r}}{r}=\lim_{r\to0}\frac{\psi(n-r+1)-\psi(r+1)}{\binom{n}{r}}=\psi(n+1)+\gamma=H_n$$

$\endgroup$
1
$\begingroup$

Although $\binom{n}{r}$ is usually only defined for $r\in\mathbb{Z}$, this would be a natural extension for non-integral $r$. With this extension, and this answer, which says that $\frac{\Gamma'(x)}{\Gamma(x)}=-\gamma+H(x-1)$, $$ \begin{align} \lim_{r\to0}\frac{\mathrm{d}}{\mathrm{d}r}\binom{n}{r} &=\lim_{r\to0}\binom{n}{r}\left[\frac{\Gamma'(n-r+1)}{\Gamma(n-r+1)}-\frac{\Gamma'(r+1)}{\Gamma(r+1)}\right]\\ &=\frac{\Gamma'(n+1)}{\Gamma(n+1)}-\frac{\Gamma'(1)}{\Gamma(1)}\\[6pt] &=(H_n-\gamma)-(H_0-\gamma)\\[12pt] &=H_n \end{align} $$ Thus, $$ \begin{align} \lim_{r\to0}\frac1r\left(1-\frac1{\binom{n}{r}}\right) &=\lim_{r\to0}\frac1{\binom{n}{r}}\frac{\binom{n}{r}-1}{r}\\ &=\lim_{r\to0}\frac1{\binom{n}{r}}\frac{\binom{n}{r}-\binom{n}{0}}{r-0}\\ &=\left.\frac1{\binom{n}{r}}\frac{\mathrm{d}}{\mathrm{d}r}\binom{n}{r}\right|_{r=0}\\[9pt] &=H_n \end{align} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.